Reconstitution of a bacterial periplasmic permease in proteoliposomes and demonstration of ATP hydrolysis concomitant with transport. - Bishop, L (1989)
The histidine periplasmic permease of Salmonella typhimurium has been partially purified and reconstituted into proteoliposomes. In this in vitro preparation, transport activity is completely dependent on the presence of all four permease proteins (HisJ, HisQ, HisM, and HisP) and on internal ATP. The reconstituted system shows initial rates of transport that are comparable to those obtained with right-side-out membrane vesicles and it establishes a 100-fold concentration gradient for histidine. Proteoliposomes also transport histidine when GTP replaces ATP. Proteoliposomes do not catalyze significant ATP hydrolysis until histidine transport is initiated by addition of substrate along with HisJ, the water-soluble histidine-binding protein. Both initially and throughout the course of substrate transport there is a concomitant hydrolysis of ATP, with an apparent stoichiometry (ATP/histidine) of 5:1. These experiments demonstrate directly that ATP is the source of energy for periplasmic permeases, thus resolving previous controversies on this topic.